The rise of self-judging essential security interest clauses in international investment agreements - Karl P. Sauvant; Mevelyn Ong (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2016)
Self-judging "essential security interest" clauses permit a state to act as "it considers necessary" for the protection of such interests. This Perspective examines trends in their diffusion and scope, and outlines suggestions for treaty drafters to consider when balancing the desire for regulatory sovereignty with the need for legal stability.
Keywords: 330